The Role of the Autonomic Nervous System in the Pathophysiology of Obesity - Guarino, Daniela; Nannipieri, Monica; Iervasi, Giorgio; Taddei, Stefano; Bruno, Rosa Maria (Frontiers in Physiology, 2017)
Obesity is reaching epidemic proportions globally and represents a major cause of comorbidities, mostly related to cardiovascular disease. The autonomic nervous system dysfunction has a two-way relationship with obesity. Indeed, alterations of the autonomic nervous system might be involved in the pathogenesis of obesity, acting on different pathways. On the other hand, the excess weight induces autonomic nervous system dysfunction, which may be involved in the haemodynamic and metabolic alterations that increase the cardiovascular risk of obese individuals, i.e.hypertension, insulin resistance and dyslipidemia. This article will review current evidence about the role of the autonomic nervous system in short-term and long-term regulation of energy homeostasis. Furthermore, an increased SNS activity has been demonstrated in obese patients, particularly in the muscle vasculature and in the kidneys, possibily contributing to increased cardiovascular risk. Selective leptin resistance, obstructive sleep apnea syndrome, hyperinsulinemia and low ghrelin levels are possible mechanisms underlying sympathetic activation in obesity. Weight loss is able to reverse metabolic and SNS alterations associated with obesity. Given the crucial role of autonomic dysfunction in the pathophysiology of obesity and its cardiovascular complications, vagal nerve modulation and sympathetic inhibition may serve as therapeutic targets in this condition.